The Effect of Online Review Learning Methods on Nursing Students during COVID-19 Pandemic - Nur Hidayati; Esti Andarini; Yudisa Diaz Lutfi Sandi; Resti Yulianti Sutrisno (Babali Nursing Research, 2022)
Introduction: In the pandemic era, online learning is quickly overtaking traditional classroom instruction in popularity. Dealing with pandemic conditions while still prioritizing the ultimate goal of optimal learning, namely by using online learning combined with a review approach. The purpose of this research is to examine the effect of the practicum method with an online review approach of the Anatomy and Physiology Course compared to an online mini-lecture for nursing students at Universitas Muhammadiyah Lamongan, Indonesia. Methods: Adopted pre-experimental prepost test design used two group. Counted participant were recruited from nursing students in Universitas Muhammadiyah Lamongan in the academic year 2020 and 2021 in first semester by purposive sampling. Analyzed using Mann Whitney to cultivate midterm and final exams score. Results: The mean and standart deviation of intervention group (76.32 ± 9.63) exhibited significant compared to control group 63 ± 9.80 with p value= 0.001. Conclusion: The online review practice method has been proven to increase student scores during the pandemic compared to usual online review. Preliminary findings from this study show how COVID-19 has impacted first-year students' online learning behaviors and suggest online review learning as a strategy for maintaining students' learning during the pandemic.